2019
DOI: 10.1634/theoncologist.2018-0905
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Patients with DNA Repair Pathway Mutations Treated with a PARP Inhibitor

Abstract: Background Molecular analysis has revealed four subtypes of pancreatic ductal adenocarcinoma (PDAC). One subtype identified for the presence of DNA damage repair deficiency can be targeted therapeutically with the poly (ADP‐ribose) polymerase (PARP) inhibitor olaparib. We performed a single institution retrospective analysis of treatment response in patients with PDAC treated with olaparib who have DNA damage repair deficiency mutations. Subjects, Materials, and Methods Patients with germline or somatic mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…Genes located at 13q12.13 contain BRCA2 which plays an important role in homologous DNA repair pathway. It has been recently reported that PDAC patients with deficient homologous DNA repair system resulted from germline or somatic mutations on BRCA1 or BRCA2 are susceptible to Poly (ADP-ribose) polymerase (PARP) inhibitor therapy [ 24 , 25 ]. However, cases harboring targetable mutations occur at quite low frequency (4–7%) [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Genes located at 13q12.13 contain BRCA2 which plays an important role in homologous DNA repair pathway. It has been recently reported that PDAC patients with deficient homologous DNA repair system resulted from germline or somatic mutations on BRCA1 or BRCA2 are susceptible to Poly (ADP-ribose) polymerase (PARP) inhibitor therapy [ 24 , 25 ]. However, cases harboring targetable mutations occur at quite low frequency (4–7%) [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…In patients with gBRCA1 -PDAC, prior studies have found a high prevalence of somatic BRCA1 mutations, albeit their findings were limited in the sample size. Yurgelun et al described concomitant sBRCA1 mutations in one (33%) out of three patients [ 23 ], whereas Borazanci et al observed the same finding in one of two PDAC tumors [ 24 ]. Our results indicate that second sBRCA1 mutations are infrequently associated with gBRCA1 P/LPVs and occurred in only two (10.5%) of 19 patients in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 However, case reports of ATM-mutated pancreatic cancers have not shown disease control with PARP inhibitor maintenance therapy. 26,27 Indeed, PARP inhibitor monotherapy was only cytostatic but did not induce cell killing in ATM-deficient preclinical pancreatic cancer cell models. 28 There are preclinical data suggesting efficacy of ATM inhibitors, ATR inhibitors, and CHK1 inhibitors 29 or of combination therapies of multiple DNA damage repairtargeting therapies, 24 and there are ongoing early-phase clinical trials at this time.…”
Section: Practical Applicationsmentioning
confidence: 99%